Epilepsy: addressing the transition from pediatric to adult care - Rajendran, Seetha (Adolesc Health Med Ther, 2016)
Adolescence is a period of rapid change, both physical and psychosocial for any young person. It can be challenging when they have ongoing health problems and when their care needs to be transitioned to the adult health care system. Transition should be a planned process of addressing the medical and associated comorbid conditions from pediatric to adult care in a coordinated manner. In most cases, the young person and their family are well known to the pediatrics services and have built a relationship based on trust and often friendship over many years. Understandably, there is significant apprehension about moving from this familiar setting to the unknown adult services. Apart from having a sound knowledge of specific childhood epileptic conditions and associated comorbid disorders, it is important that both the pediatric and adult epilepsy teams are motivated to provide a successful and safe transition for these patients. It is essential that transition is seen as a continual process and not as a single event, and good preparation is the key to its success. It is also important that general practitioners are closely engaged to ensure successful transition. An overview of how to effectively address transition in epilepsy, different models of transition, transition of relevant epilepsies, and their management is discussed.